Os evangélicos segundo a imprensa: discursos e enquadramentos na produção da Folha de S. Paulo e O Globo de 1985 a 2020 - Alvim, Mariana Freitas (2022)
This research investigates the production of journalistic discourses about Brazilian evangelicals. The increasing visibility of these religious groups since the 1980s is due, in part, to the rise of press interest in them. Previous research indicated, through discourse analysis, that journalistic content about evangelicals was predominantly marked by irony, delegitimization, stereotypes and their designation as the “other”. This discourse analysis focuses on two leading printed newspapers, O Globo and Folha de S. Paulo, a segment of journalism that was not much covered in previous researches. The sample consists of cover stories published in 1985, 1990, 1995, 2000, 2005, 2010, 2015 and 2020, totaling 244 texts. The analysis focused on the nature of discourse about evangelicals, seeking to answer when such religious groups become a matter of journalistic attention. The corpus was organized into three major structuring discourses of newspapers coverage: the discourse of expansion, in which evangelical growth in several areas is identified and placed as a possible threat to catholicism and religious tolerance in the country; that of exploitation, in which the relationship between the churches and their followers, when mediated by money, is sewn by a moral judgment; and that of public space, in which the presence of evangelicals in politics and in public areas reveals tensions over their impact on the wider society. Each of these three discourses is composed of three news frames (totaling nine news frames), a theoretical-methodological approach that proposes to typify, in journalistic content, patterns of text structuring and recurrent themes. Quantitatively and qualitatively, it was found that the Universal Church was by far the most focused church and that evangelical pastors and politicians predominated as sources, to the detriment of evangelical followers. It was also found that specialists, members of the Catholic hierarchy and the hierarchy of historic evangelical churches, participated, as sources, in the construction of predominant discourses about evangelicals in the newspapers, as well as did statements and actions of judicial bodies